2018
DOI: 10.1037/edu0000245
|View full text |Cite
|
Sign up to set email alerts
|

Multiple pathways to success: An examination of integrative motivational profiles among upper elementary and college students.

Abstract: Two studies were conducted with distinct samples to investigate how motivational beliefs cohere and function together (i.e., motivational profiles) and predict academic adjustment. Integrating across motivational theories, participants (NStudy 1 = 160 upper elementary students; NStudy 2 = 325 college students) reported on multiple types of motivation (achievement goals, task value, perceived competence) for schooling more generally (Study 1) and in science (Study 2). Three profiles characterized by Moderate-Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(55 citation statements)
references
References 90 publications
4
41
0
6
Order By: Relevance
“…In line with other recent studies of students' motivational beliefs (e.g., Andersen & Chen, 2016;Linnenbrink-Garcia et al, 2018;Perez, Dai, et al, 2019;Perez, Wormington, et al, 2019;Robinson et al, 2018), we used latent profile analysis (LPA) to answer the research questions. As with latent class analysis, LPA is a person-centered approach (Bergman & Trost, 2006;Collins & Lanza, 2010) and a form of mixture modeling that tests the fit and significance of a certain number of types or latent profiles among individuals within a data set (Goodman, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In line with other recent studies of students' motivational beliefs (e.g., Andersen & Chen, 2016;Linnenbrink-Garcia et al, 2018;Perez, Dai, et al, 2019;Perez, Wormington, et al, 2019;Robinson et al, 2018), we used latent profile analysis (LPA) to answer the research questions. As with latent class analysis, LPA is a person-centered approach (Bergman & Trost, 2006;Collins & Lanza, 2010) and a form of mixture modeling that tests the fit and significance of a certain number of types or latent profiles among individuals within a data set (Goodman, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond that, these motivational factors likely work together to influence students’ decisions to persist in or leave STEM fields. Indeed, students often hold multiple motivational beliefs simultaneously (e.g., Andersen & Chen, ; Bøe & Henriksen, ; Conley, ; Linnenbrink‐Garcia et al, ). For example, it is possible that a student may have a high interest in pursuing a STEM career but may also perceive high costs associated with pursuing such a career.…”
Section: Introductionmentioning
confidence: 99%
“…In sum, more research is needed to understand how competence beliefs, task values, and perceived costs combine in science and to understand how such motivational profiles relate to STEM outcomes. A handful of researchers have examined expectancy‐value beliefs using person‐oriented methods (Andersen & Chen, ; Bøe & Henriksen, ; Chow et al, ; Conley, ; Linnenbrink‐Garcia et al, ; Viljaranta, Nurmi, Aunola, & Salmela‐Aro, ; Wang et al, ) and only two of these studies included competence beliefs and task values along with a measure of perceived costs (Bøe & Henriksen, ; Conley, ) in the profile analysis. Furthermore, only a few studies focused on science expectancy‐value beliefs in particular (Andersen & Chen, ; Bøe & Henriksen, ; Chow et al, ; Linnenbrink‐Garcia et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A person-centered approach to identifying motivational profiles Unlike variable-centered approaches, which mainly examine the ability of one or more variables to predict an outcome variable, a person-centered approach focuses on testing the relationships among variables at an individual level, and classifying those who share homogeneous characteristics into groups on the basis of such characteristics (Bergman, 2001). Recently, an increasing number of studies have adopted person-centered approaches in response to calls to investigate naturally occurring multiple motivational profiles in face-to-face settings (eg, Corpus & Wormington, 2014;Linnenbrink-Garcia et al, 2018). In general, these studies identified two sets of categorizations, one with four clusters (or profiles) (eg, Rothes, Lemos, & Gonçalves, 2017;Wormington, Corpus, & Anderson, 2012) and the other with three (Ratelle et al, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%